URGENCY OF PARTNERS' BUDGETING IN MEDIATING WORK PROGRAMS ON MANAGERIAL PERFORMANCE - Kurniawan, Shidiq Patria; Marwan, Jubery; Franky (Moestopo International Review on Social, Humanities, and Sciences, 2023)
The output achievements and results of an activity or program are the work of the agency, as an effort to achieve the goals and objectives that have been set by the main tasks and functions of the agency. To achieve good performance, of course, proper strategic management is needed, so that if the organization's work program can be implemented into the budgeting of its activities, of course, it will influence and have a good impact on the organization's performance. The analytical method used is the analysis of direct and indirect effects (path analysis). The data source uses primary data which is carried out by taking samples directly from correspondents through filling out questionnaires. The results of the study obtained the following conclusions: (1) The work program does not affect partner budgeting. (2) Partner budgeting has a significant effect on managerial performance. (3) Work programs have a significant effect on managerial performance. (4) Work programs on managerial performance through partner budgeting have a significant effect and a positive impact.